High-performance electromagnetic wave absorption by designing the multilayer graphene/thermoplastic polyurethane porous composites with gradient foam ratio structure. (October 2019) - Wang, Chaozhi; Li, Jiang; Guo, Shaoyun
Abstract: An excellent electromagnetic wave absorbing material (EWAM) should possess both wider effective absorption bandwidth (EB) and lower minimum reflection loss ( RL min ), which depends on good impedance matching between the EWAMs and air and strong attenuation of electromagnetic wave (EW) inside the absorber. In this work, single-layer graphene/thermoplastic polyurethane (TPU) porous composites with different foam ratio and gradient foam ratio multilayer graphene/TPU porous composites with different number of layers were prepared. Not only were the EW-absorbing properties and mechanism of these composites investigated, but the mechanical properties were also examined. Compared to the single-layer samples with the same average foam ratios at the same thickness, the multilayer samples showed wider EB, 5.6, 4.6, 4.4 GHz for 3L, 4L and 5L, respectively. By designing the multilayer structure of gradient foam ratio, it provides a novel path for the preparation of EWAMs with strong absorption capacity, wider EB, light weight and excellent mechanical properties.